Studi pendahuluan silika amorf sekam padi sebagai scaffold sintetis bone graft: efeknya terhadap aktivitas sel osteoblas (In-vitro) - Didin Erma Indahyani; Zahreni Hamzah; Pujiana Endah Lestari (Jurnal Material Kedokteran Gigi, 2012)
Synthetic bone graft material was developed as a scaffold that serves to template the formation of bone. The ideal scaffold should be biodegradable, osteoindukctive, and osteoconductive. Silica proven to support and promote bone growth. Rice husk contains silica is quite high. The purpose of this study is to analyze the amorphous silica from rice husk as synthetic bone graft material (scaffold), particularly on osteoblast activity in vitro. The research was conducted by isolating silica from rice husk.The results of isolation would be conditioned on the culture medium of primary osteoblasts. Primary osteoblast cultures derived from rat calvaria wistar age of 2 days, growing in Alpha-Modified Eagle Medium (α-MEM) (as a negative control), α-MEM in conditioning with silica 58s (as a positive control) and α-MEM that conditioned with silica from rice husk (as treatment group). Osteoblast activity was observed by analyzing the expression of alkaline phosphatase, using Alkaline phosphatase Kits at days 7 and 14. The results obtained that the rice husk silica were significantly (p <0.05) has the expression of alkaline phosphatase higher than the control group and potitif group. This may imply that the amorphous silica of rice husk affects the increase in osteoblast activity in vitro. It was concluded that rice husk silica increases osteoblast cell activity that is potentially as scaffold for bone graft synthetic material.